2023
DOI: 10.20452/pamw.16444
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution and long-term risk of hospital admission due to chronic obstructive pulmonary disease exacerbations in Poland: a time-stratified, case-crossover study

Abstract: What's new?Growing evidence from studies across the world has attributed substantial disease burden to air pollution. Gaseous and particulate air pollution in Poland is an important public health problem, but the disease burden related to air pollution is largely unknown. In Poland, there is a lack of long-term, multi-city studies linking air pollution to objective healthcare measures.People with chronic lung diseases, such as chronic obstructive pulmonary disease (COPD), are most susceptible to ambient air po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Tobacco smoking, the first known cause of COPD, and air pollution's roles in developing chronic respiratory diseases are still not marginal [110,111]. Strategies for reducing COPD incidence and the severity of the disease (including preventing AECOPD) may reduce the amount of severe AECOPD patients requiring an ICU admission, meaning a clear benefit for the patient's health but also representing a strategy for reducing the economic impacts of COPD management and ICU stays [112][113][114][115][116][117][118][119]. Future research is needed to explore all these unmet questions about COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco smoking, the first known cause of COPD, and air pollution's roles in developing chronic respiratory diseases are still not marginal [110,111]. Strategies for reducing COPD incidence and the severity of the disease (including preventing AECOPD) may reduce the amount of severe AECOPD patients requiring an ICU admission, meaning a clear benefit for the patient's health but also representing a strategy for reducing the economic impacts of COPD management and ICU stays [112][113][114][115][116][117][118][119]. Future research is needed to explore all these unmet questions about COPD.…”
Section: Discussionmentioning
confidence: 99%
“…This findings were similar to the previous studies. Dabrowiecki P et al 20 reported that during 21 days after exposure, an increase of 10 μg/m 3 in SO 2 and PM 10 was associated with an increase of 14.5% (95% CI: 3.8–26.2%) and 2.8% (95%CI: 0.8–4.9%) in COPD hospital admissions, respectively. Ghanbari et al 21 reported that during 1 year exposure, an increase of 10 μg/m 3 in SO 2 was associated with an increase of 0.5% (95% CI: 0%–1%) in COPD hospital admissions.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous epidemiological studies have demonstrated that short‐ and long‐term exposure to air pollution is associated with COPD hospital admissions, acute exacerbation and mortality. 5 , 6 , 7 Dong et al 8 demonstrated that a 10‐μg/m 3 increase in PM 10 , SO 2 and NO 2 was associated with a 0.25% (95%CI: 0.01–0.49%), 1.67% (95%CI: 0.54–3.93%) and 1.37% (95%CI: 0.25–2.51%) increase in COPD outpatient visits, respectively. Zhang et al 9 found that every 10‐μg/m 3 increase in pollutants, the majority of the summary estimates for COPD hospital admissions were in the order of (ozone 3) O 3 > (particulate matter with aerodynamic diameter ≤ 2.5 um) PM 2.5 > NO 2 > PM 10 > SO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Ambient air pollution could be linked to 8% to 10% of COPD admissions. [7] Another vulnerability caused by air pollution that calls for a serious concern, includes intra-uterine exposure to air pollutants and specially its effects on prenatal development. During both the prenatal and postnatal period, the window of vulnerability lies between the growth and developmental phases of the respiratory system of a fetus and extends till early infancy.…”
Section: Letter To the Editormentioning
confidence: 99%